Effects of Lycium barbarum on bacterial translocation in thioacetamide-induced liver injury in rats. (December 2015) - Bilgic, Y; Harputluoglu, MMM; Kutlu, O; Demirel, U; Gul, M; Otlu, B; Temel, I; Gursoy, S; Dertli, R; Selcuk, EB; Yilmaz, I; Kilis, T
Background and study aim: The aim of the present study was to investigate the effects of Lycium barbarum (LB) on bacterial translocation (BT) frequency in thioacetamide (TAA)-induced liver injury in rats. Materials and methods: Group 1 was the control. In group 2 (TAA), rats received TAA daily for 3 days. In group 3 (TAA+LB), Lycium barbarum was administered orally 25 mg/kg for 21 days prior to the first TAA injection. In group 4 (LB), rats received only Lycium barbarum . Results: In our study, Lycium barbarum treatment did not attenuate liver damage. Lycium barbarum treatment decreased ileal E. coli counts and intestinal damage but it did not alter BT frequency. Conclusions: In conclusion, the effects of Lycium barbarum on BT may be related to ongoing severe liver damage in this model.